FAKTOR-FAKTOR PENENTU PEMBIAYAAN HIJAU DI BANK-BANK INDONESIA: BUKTI DARI UKURAN, PROFITABILITAS, DAN KECUKUPAN MODAL - Alia Rezki Amalia; Muh. Qodri Alfairus; Nur Abshari Abbas (Universitas Ichsan Sidenreng Rappang, 2026)
Abstract This study aims to analyze the influence of bank size, profitability, and capital adequacy on the volume of green financing in Indonesian banking companies. Green financing plays a crucial role in supporting the transition toward a sustainable economy. However, the internal factors of banks that drive its allocation still require further investigation. This research employs a quantitative approach using secondary data collected from financial reports and sustainability reports of banks listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. Through purposive sampling, eight banks were selected as samples based on data completeness criteria, resulting in a total of 40 observations. The analytical technique used is panel data regression with the Random Effect model. The results show that bank size and profitability have a positive and significant effect on the volume of green financing. In contrast, capital adequacy is not proven to have a significant effect. These findings indicate that large banks and highly profitable banks tend to be more active in channeling green financing, while the level of capital ratio is not yet a main determinant in the allocation of green credit in Indonesia. Bank size and profitability are the primary drivers of green financing in the Indonesian banking sector, whereas capital adequacy has not played a significant role. This study recommends that regulators strengthen incentive mechanisms that link capital adequacy with green financing performance, as well as encourage banks to integrate sustainability strategies into capital allocation in a more structured manner.